1999
DOI: 10.1161/01.str.30.11.2307
|View full text |Cite
|
Sign up to set email alerts
|

Recent Heavy Drinking of Alcohol and Embolic Stroke

Abstract: Background and Purpose-Epidemiological evidence suggests that heavy alcohol consumption increases the risk for ischemic stroke, whereas light-to-moderate alcohol intake decreases the risk, but the role of different drinking patterns has remained unclear. We investigated recent light, moderate, and heavy alcohol drinking and former heavy drinking as risk factors for acute ischemic brain infarction by etiological subtype of stroke. Methods-We compared 212 consecutive patients aged between 16 and 60 years, who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
1
13

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 34 publications
2
81
1
13
Order By: Relevance
“…2 Recent heavy alcohol consumption has been found to significantly increase the risk of cardioembolic stroke, even after adjustment for hypertension, smoking, hyperlipidaemia, and diabetes. 12 Nevertheless, light-to-moderate alcohol consumption has been shown to reduce the overall risk of stroke and the risk of ischaemic stroke in men. 13 Even in male smokers, light alcohol consumption may reduce the risk of cerebral infarction and haemorrhage, while heavy drinking increases the risk of all stroke Alcohol in the LIFE study HM Reims et al subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…2 Recent heavy alcohol consumption has been found to significantly increase the risk of cardioembolic stroke, even after adjustment for hypertension, smoking, hyperlipidaemia, and diabetes. 12 Nevertheless, light-to-moderate alcohol consumption has been shown to reduce the overall risk of stroke and the risk of ischaemic stroke in men. 13 Even in male smokers, light alcohol consumption may reduce the risk of cerebral infarction and haemorrhage, while heavy drinking increases the risk of all stroke Alcohol in the LIFE study HM Reims et al subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Increased frequency and severity of atherosclerosis in the circle of Willis as well as in the middle cerebral, basilar and carotid arteries is observed in diabetics. 24 Matti Hillborm et al 25 in 1999 investigated the effect of alcohol as a risk factor for acute ischemic stroke. They found that recent (past week) heavy drinking (151-300g) but not former heavy drinking was an independent risk factor for stroke.…”
mentioning
confidence: 99%
“…ALDH-E2 involves in the oxidative pathway of alcohol metabolism (Smith, 1986;Hempel et al, 1987). Substantial evidence indicated that alcohol abuse is sever risk factor for stroke (Gill et al, 1986(Gill et al, , 1991Hillbom et al, 1999;Klatsky et al, 2001;Mazzaglia et al, 2001). ALDH2 polymorphisms play a pivotal role on hypertension (Hasi et al, 2011;Wang et al, 2013;Yokoyama et al, 2013;Hu et al, 2014), heart disease (Gu, Li, 2014;Mizuno et al, 2015) and stroke (Yao et al, 2011;Lai et al, 2012).…”
Section: Discussionmentioning
confidence: 99%